Business models for strategic innovation cross-functional perspectives - Shams, S. M. Riad 1979- (The annals of business research, 2018)
"This book extends our understanding of how different cross-functional business and management disciplines, such as innovation and entrepreneurship, strategic management, marketing and HRM, individually and collectively underpin innovation in business management. Business Models for Strategic Innovation develops insights from cross-disciplinary business knowledge streams and their cutting edge discipline-specific practical implications to create a cross-functional business innovation management model. Novel cross-disciplinary knowledge plays an imperative role in business innovation and we know that innovative management processes have significant implications for effective cross-functional management. In this context, each chapter of the book presents fresh insights on diverse business knowledge-streams as well as their applied implications on cross-functional business innovation management. Finally, centred on these cross-disciplinary business theories and their cutting edge implications, the last chapter of this book proposes a model of strategic cross-functional business innovation management process. This academically rigorous work uses innovative theoretical propositions and state-of-the-art empirical analysis in order to enable cross-functional management teams to support organisation-wide business innovation processes."--Provided by publisher